Peningkatan Keterampilan Menulis Naskah Drama melalui Pendekatan Pembelajaran Kontekstual Siswa Kelas VIII RSBI-SMP Negeri 12 Padang - Yurnelis .; Hasanuddin WS; Ermanto . (Bahasa, Sastra, dan Pembelajaran, 2013)
Abstract: The background of the research is the low ability of the students in writting the role play text, where they can’t pass the minimum mastery criterion (KKM ) yet. Type of the research is  Classroom Action Research. It is done in two (2) cycles. The act of the teaching and learning process is done by using CTL approach as mention above. Each cycle is done by integrating some CTL components and observed by the observer. The steps of the research are plan, do, observation and reflection. The datas are qualitative and quantitative. Qualitative data is collected from the observation and filed note while the quantitative data got from the result of students performance test. The conclusion  of the reasearch are( 1). There is an increasing of student’s activity in teaching and learning process after the first and the second cycle done.( 2). There is an increasing of students achievement result in wrttingrole play text  from 68,38 in pra cycle, means that only 40% of the students pass the KKM . It increase into 73,75 at the first cycle or 64 % of students pass the KKM. At  second cycle  the avarage  students value is 88,25, means that 100%  of the students can and pass the minimum mastery criteria (KKM). Kata Kunci: keterampilan menulis, naskah drama, pendekatan pembelajaran Kontekstual